Protective effect by aqueous extract of Phyllanthus amarus Linn., phyllanthin and nirocil against carbontetrachloride-induced liver and brain toxicity - Venkatesan P.; Satyan K.S.; Sudheer Kumar M.; Prakash A. (My University, 2025)
Effect of carbontetrachloride treatment on hepatic and brain antioxidant status in rats pretreated with aqueous extract of Phyllanthus amarus Linn. (Euphorbiaceae), nirocil (a tablet made up of aqueous extract of P. amarus), phyllanthin (a bioactive lignan from P. amarus), and silymarin were studied. Plasma aspartate aminotransferase and alanine aminotransferase were estimated to monitor the extent of hepatocellur damage. Tissue lipid peroxide, ascorbic acid and total protein levels were used as the markers for functional and antioxidant efficiency of liver and brain cells. Phyllanthin reversed the elevated plasma aminotransferase levels but did not affect hepatic antioxidant status. In all the paradigms tested for hepatoprotection, nirocil, Silymarin and aqueous extract (90 mg/kg) showed significant protection. There was a drastic impairment in the functional and antioxidant status of brain on treatment with carbontetrachloride. None of the drugs except silymarin showed good protection against carbontetrachloride-induced lipid peroxidation in the brain, but all these produced a significant increase in the protein levels. All the drugs administered, augmented the ascorbate levels in liver and brain, with the aqueous extract of P. amarus clearly outdoing the others.